Immobilization of Amino Acids Leucine and Glycine on Polypyrrole for Biosensor Applications: A Density Functional Theory Study - Hermawan K. Dipojono; Irna Safitri; Nugraha Nugraha; Eko Mursito Budi; Nuryanti Nuryanti; Adhitya G. Saputro; Melanie Y. David; Hideaki Kasai (Journal of Mathematical and Fundamental Sciences, 2011)
Adsorption based on the immobilization of amino acids, i.e. leucine and glycine, on the surface of undoped polypyrrole (Ppy) is investigated. Calculations are done based on density functional theory using Gaussian03 software and applying GGA with 6-31G(d) basis set and exchange-correlation model of PBE (Perdew, Burke, Ernzerhof) level of theory. The energy of the Ppy doped with amino acids are minimized with respect to the orientation and distance of the amino acids to the Ppy. Neutral leucine carboxyl shows greater binding energy as compared to that other leucine configurations. It has adsorption energy of 0.25 eV at optimum distance of 2.2 Ã… from the surface of Ppy. As for the glycine, the zwitterionic carboxyl exhibits the strongest binding energy among other glycine configurations. It has adsorption energy of 0.76 eV at optimum distance of 1.7 Ã… from the surface of Ppy. The adsorption processes for both amino acids should proceed easily because the activation barriers are either absent or very small.